Educational research on solving real tax problems in cross-border e-commerce - Vitalievna Salmina, Svetlana (2021)
The paper considers current taxation problems in cross-border electronic commerce in goods, the share of which in total trade continues to grow. Considering the field of economics as a part of university education, which can play a prominent role in solving the current problems, we suggests possible ways of regulating the cross-border e-commerce taxation by involving digital platforms in the taxation process and making them fully or partially liable for tax obligations. In addition, the establishment of university educational courses in the field of economics has been proposed as a way to improve the economic situation